Virus‐Dependent Geographic Structure of Co‐Circulating Viruses in a Single Bat Species - Avery L. Holmes; Alice Broos; Daniel J. Becker; Jorge E. Carrera; Maxwell J. Farrell; Rita Ribeiro; Carlos Tello; Laura M. Bergner; Daniel G. Streicker (Molecular Ecology, 2026)
Understanding the spatial spread of viruses within wildlife populations is often a key component of disease management efforts. Viral spread is likely constrained by host ecology, but inter‐virus differences in infection strategy might allow some viruses to overcome these constraints, leading to divergent population structures within a common host environment. We studied the phylogeographic structure of six virus taxa (dependoparvovirus, deltavirus, mastadenovirus, betaherpesvirus and two lineages of rabies virus) circulating in common vampire bats ( Desmodus rotundus ) in Peru, finding that viral population structure is inconsistently constrained by host ecology. Specifically, while bat travel distance structured the genetic diversity of betaherpesvirus and two lineages of rabies virus, other viruses were instead constrained by anthropogenic factors (dependoparvovirus), or had weakly defined population structure (mastadenovirus). The genetic structure of all viruses was affected by a measure of human travel difficulty between sites, but effects varied in size and direction. Distinct drivers of viral population structure within the same host species imply that virus infection strategy can outweigh host ecological connectivity, acting as a key determinant of geographic spread. Because barriers to gene flow generalise poorly between viruses, whether a tractable virus can illuminate host population structure or predict the spread of high‐impact viruses depends on individual virus biology.